2007
DOI: 10.1016/j.devcel.2007.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Unequal Centrosomes Drive Spindle Orientation in Asymmetrically Dividing Drosophila Neural Stem Cells

Abstract: Stem cell asymmetric division requires tight control of spindle orientation. To study this key process, we have recorded Drosophila larval neural stem cells (NBs) engineered to express fluorescent reporters for microtubules, pericentriolar material (PCM), and centrioles. We have found that early in the cell cycle, the two centrosomes become unequal: one organizes an aster that stays near the apical cortex for most of the cell cycle, while the other loses PCM and microtubule-organizing activity, and moves exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
309
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(326 citation statements)
references
References 54 publications
16
309
0
1
Order By: Relevance
“…Mitotic spindles are perceived as a symmetric structure connecting the kinetochore of the duplicated chromatids with equal tension before separation (11,27). Conversely, asymmetric cell divisions were observed in neural and male germ stem cells in which the mother centrosome oriented toward the stem cell niche and the daughter centrosome migrated through chromosomes to the opposite side of the mother centrosome (36,37).…”
Section: Ibpr001 and Mln8237 Results In An Asymmetric Association Of Hmentioning
confidence: 99%
“…Mitotic spindles are perceived as a symmetric structure connecting the kinetochore of the duplicated chromatids with equal tension before separation (11,27). Conversely, asymmetric cell divisions were observed in neural and male germ stem cells in which the mother centrosome oriented toward the stem cell niche and the daughter centrosome migrated through chromosomes to the opposite side of the mother centrosome (36,37).…”
Section: Ibpr001 and Mln8237 Results In An Asymmetric Association Of Hmentioning
confidence: 99%
“…Asymmetric cell divisions are well documented during the differentiation of stem cells (25), and in some cases the mother centrosome has been found to associate specifically with the stem cell during asymmetric divisions (26)(27)(28). Therefore, the asymmetric inheritance of pericentrosomal materials could potentially influence the outcome of stem cell differentiation decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the Pins-Galphai-Mud complex is thought to anchor the aster of one of the spindle poles during mitosis (Bowman et al, 2006;Izumi et al, 2006;Siller et al, 2006). Combined live imaging of spindle assembly and centrosome function has shown that spindle orientation in larval NBs is determined, at least partially, from early interphase, much earlier than any of the known polarized markers can be seen at the apical cortex of the cell (Rebollo et al, 2007;Rusan and Peifer, 2007). Soon after cytokinesis, both centrosomes migrate to the nearest cortex, which roughly coincides with the region where apical markers were last localized.…”
Section: The Asymmetric Division Machinery Of Drosophila Nbsmentioning
confidence: 99%